Transport of ribavirin across the rat and human placental barrier: Roles of nucleoside and ATP-binding cassette drug efflux transporters - Karbanova, S; Cerveny, L; Jiraskova, L; Karahoda, R; Ceckova, M; Ptackova, Z; Staud, F (Biochemical pharmacology, 2019)
Ribavirin is a broad-spectrum nucleoside-derived antiviral drug used in combination pharmacotherapy treatment of hepatitis C virus infection. Current evidence indicates that ribavirin-associated teratogenicity is not significant in humans, but more information about the developmental toxicity and mechanisms involved in ribavirin placental kinetics is required to assure its safe use in pregnancy. Thus, we have investigated potential roles of equilibrative nucleoside transporters (ENTs, SLC29A), Na+-dependent influx-mediating concentrative nucleoside transporters (CNTs, SLC28A), and ATP-binding cassette (ABC) efflux pumps, in ribavirin placental pharmacokinetics. Our data indicate that ENT1 participates in uptake of ribavirin by BeWo cells, fresh human placental villous fragments and microvillous plasma membrane (MVM) vesicles while activity of CNTs (probably CNT2) was only observed in BeWo cells. In situ dual perfusion experiments with rat term placenta in an open circuit setup showed that ENT inhibition significantly decreases total ribavirin maternal-to-foetal and foetal-to-maternal clearances. In contrast, no contribution of ABC transporters, p-glycoprotein (ABCB1), breast cancer resistance protein (ABCG2), or multidrug resistance-associated protein (ABCC2) was detected in assays with MDCKII cells overexpressing them, or in closed circuit dual perfusion experiments with rat term placenta. In summary, our data show that ribavirin placental pharmacokinetics are largely controlled by ENT1 activity and independent of ABCB1, ABCG2, and ABCC2 efflux pumps.
Keywords: psi; transport proteinů; Pregnancy; Humans; Dogs; druhová specificita; Nucleosides; protein spojený s mnohočetnou rezistencí k lékům 2; Multidrug Resistance-Associated Protein 2; nukleosidy; Protein Transport; Nucleoside transporters; Placenta; Dose-Response Relationship, Drug; Female; ABC transportéry; ribavirin; krysa rodu Rattus; lidé; zvířata; Equilibrative Nucleoside Transporter 1; potkani Wistar; buňky MDCK; ženské pohlaví; Rats, Wistar; ATP-Binding Cassette Transporters; Madin Darby Canine Kidney Cells; antimetabolity; těhotenství; Species Specificity; nádorové buněčné linie; ABC transporters; ekvilibrační přenašeč nukleosidů 1; Rats; vztah mezi dávkou a účinkem léčiva; Animals; Cell Line, Tumor; Antimetabolites; placenta; Ribavirin